A critical appraisal of Freud's ideas on man and personality - Abdul Razak, Mohd Abbas; Ismail, Nik Ahmad Hisham (London Churchill College Publisher, 2020)
Since ancient times, scholars in the West have shown great enthusiasm towards understanding the subject on man and personality. Driven by this zeal, there appeared a multitude of theories discussing man and his nature. Though the various concepts on man showcased by the scholars complemented one another, at times their ideas also contradicted and discredited one another. Sigmund Freud (1856-1939) the founding father of psychoanalysis presented to the world a concept on man and his personality which remains controversial to the present day. In realizing the fact that Freud’s ideas have a huge impact on modern psychology and people in the West, the researchers of this study would like to revisit some of his ideas on man and personality. Upon making an exposition of his ideas, the researchers too would like to carry out an appraisal on Freud and to identify some of the underlying factors that led him towards conceptualizing a theory on man which is not only degrading to man’s position as the most intelligent of God’s creation but also an unprecedented one in the history of modern psychology.